Peter Blos papers - Blos, Peter
Historical account of the Hietzing School founded by Dorothy T. Burlingham, Anna Freud, and Eva Marie Rosenfeld in Wattmangasse, Vienna, Austria, in 1927, at which Blos and Erik H. Erikson taught until its closing in 1932; two issues of the school's Christmas literary and art publication; teaching materials prepared by Blos and Erikson; and a photograph and memorial from a reunion of former students and teachers in London, England, in 1972.
Psychoanalyst.
Collection material in English.
Forms part of: Sigmund Freud collection.
Keywords: Burlingham, Dorothy T; Erikson, Erik H. -- 1902-1994.; Freud, Anna, -- 1895-1982.; Rosenfeld, Eva Marie, -- 1892-1977.; Hietzing School; Education -- Austria -- Vienna; Private schools -- Austria -- Vienna; Psychoanalysis; Psychoanalysts